A SYMBOLIC MEANING ON DEKKE SIMUDUR-UDUR IN BATAK TOBA WEDDING CEREMONY - Debby Aritonang; Muhammad Natsir (LINGUISTICA, 2022)
This study aims at findings out how gender study on Batak Toba Wedding Ceremony that show on YouTube at Semiotics with type of Sylvia Pierce’s (1899) theory casual effect. The objective of the study to investigate what symbols of Dekke Simudur-udur in wedding ceremony of Batak Toba cycle of and howthe realization of dekke have a  holy symbols in married life. A descriptive qualitative design is applied in the research with scientific individual experience life by textual analysis of Neuman, (2007). The procedure of collecting data is analyze the Video in TouTube from watching the video and take the utterences of giver of Dekke simudur-udur for bride and groom. The research findings are found based on Pierce's theory, they are joy, blessing, prosperity, loyalty, and harmony. In conclusion,several regulations have been established for traditional Batak weddings, particularly in the section on handing over dekke simudur-udur. Only the woman's family and the bride's parents' brothers are permitted to participate in the procession